INNOVATIVE TECHNOLOGIES AND TACTICAL APPROACHES IN THE TREATMENT OF ABDOMINAL INJURIES. - Mustafakulov Ishnazar Boynazarovich; Mamarajabov Sobirjon Ergashevich; Djurayeva Zilola Aramovna (Research Focus International Scientific Journal, 2022)
The authors proposed active surgical tactics as "damage control" in traumatic liver injuries. The method of "damage control" in SFRICAN used since 2006 as the only method of saving the life of patients with traumatic injuries of the liver in the IV and V degree (for E. Moore, 1986). In the departments of emergency surgery STRNCMP 2008 – 2018 127 operated patients with liver trauma. Of these, 19 (14,96%) patients with severe liver injuries of IV and V degree of damage by E. Moore. The effectiveness of multi-stage tactics was evaluated by the level of mortality and the number of purulent-septic complications. The results of surgical treatment of 19 patients with massive liver injuries, aged 17 to 50 years, were analyzed. The median age was 26 years. There were 11 men and 8 women. The average assessment of the severity of damage on the ISS scale was 34 points (17-76), E. Moore IV and V degree of damage. The average blood loss was 2850 ml (1750-3850 ml). All patients underwent multi-stage laparotomy with gauze (film) tamponade, the average number of operations per 1 person 2,7 (2-5), suturing of the liver wound with tamponade (13), extensive hepatotomy and vascular ligation (3), atypical resection (2), stitching of large major vessels with taponade (1). The average bed/day in the intensive care unit is 13 (3-16), and the average bed/day in the clinic is 25 (3-28). Mortality was 26,3% (5 out of 19), mainly purulent-septic complications and multiple organ failure. Multi-stage surgical tactics "damage control" in isolated and combined severe liver damage is an effective method in unstable patients with the risk of developing coagulopathy and multiple organ failure. The use of the "damage control" technique helped to reduce the mortality rate from acute abdominal pathology by 27,2%.